2020
DOI: 10.1016/j.heliyon.2020.e03329
|View full text |Cite
|
Sign up to set email alerts
|

A medical mystery of complex regional pain syndrome

Abstract: Complex regional pain syndrome (CRPS) is a condition of neuropathic pain, which is characterized by significant autonomic and inflammatory features. CRPS occurs in patients who have limb surgery, limb fractures, or trauma. Many patients may have pain resolve within twelve months of the inciting incident; however, a small subset progresses to the chronic form. This transitional process often happens by changing from warm CRPS with dominant inflammatory phase to cold CRPS, in which autonomic characteristics or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 91 publications
(152 reference statements)
0
42
0
2
Order By: Relevance
“…Although most cases tend to resolve within a year following the inciting trauma, some cases progress to a more severe, chronic form of the condition [ 10 ]. Development of post-surgical CRPS is not uncommon; however, little is known regarding predisposing risk-factors to surgical candidates for CRPS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although most cases tend to resolve within a year following the inciting trauma, some cases progress to a more severe, chronic form of the condition [ 10 ]. Development of post-surgical CRPS is not uncommon; however, little is known regarding predisposing risk-factors to surgical candidates for CRPS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic activation can manifest in color change, temperature change, as well as hyper-and hypohidrosis. Autonomic changes differ in warm and cold stages of the condition [4,7]. First, initial norepinephrine release wanes, leading to increased blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Common examples include physical therapy, neuropathic pain medication, anti-inflammatories, bisphosphonates, sympathetic nerve blocks, and direct neural stimulation [4,17]. Sympathetic blocks are often insufficient for most patients, and epidural clonidine may reveal adverse effects in addition to benefits [7]. Immunoglobulin infusion clinical trials were not found to be effective in CRPS management, bringing the autoimmune aspect of the disease into question [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…described that the local administration of TRPV1 antagonist had analgesic effects on pain hypersensitivity associated to a rat model of complex regional pain syndrome (CRPS) induced by ischemia. This study suggests that TRPV1 channel might have an important role on this pain syndrome, whose pathophysiology remain poorly understood ( Eldufani et al., 2020 ). Idris et al.…”
Section: Overview Of the Articles Included In This Research Topicmentioning
confidence: 94%